THE INQUIRY TRAINING LEARNING MODEL USE MIND MAPPING AND FORMAL THINKING ABILITY ON STUDENT’S SCIENCE PROCESS SKILLS - Bima Anggraini (Universitas Negeri Medan, 2017)
The aim of this research were to analyzes: the different students’s science process skills by using inquiry training learning model and using conventional learning, the different students’s science process skills in the group of students who had formal thinking ability above average and below average, and the interaction inquiry training learning model and conventional learning with formal thinking ability of the students’s science process skills. This research carried out by a quasi-experimental with using two group pretest-postest design. The population of this study was class IX SMP IT An-Nizam Medan. The sample in this research was conducted by cluster random sampling of two classes, experiment class by using inquiry training learning model and control class by using conventional learning. The instruments of this study used science process skills in the perform work form and formal thinking ability test were collected by essay test. The data was analyzed by using two-way analysis of varians. The results of this research are the different students’s science process skills of inquiry training learning model and conventional learning, the different students’s science process skills who had formal thinking ability above average and below average, and there were an interactions between the inquiry training learning model with formal thinking ability in improving students's science process skills.